The Effect of Combination Acupuncture Therapy with Administration of Red Ginger Steeping on Changes in Pain Scale and BPFS in Patients with Low Back Pain at the Jakarta Hajj Dormitory - Ali, Ahnafa Aisya Al-Syarani Nazilah; Sholihah, Imrok Atus; Prasetya, Hanung (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
Low back pain is a musculoskeletal disorder that affects the muscles, bones, joints, and connective tissues, potentially impairing function and reducing quality of life. This study aims to determine the effect of a combination of acupuncture therapy with red ginger steeping on pain scale reduction and functional improvement in patients with low back pain. A quasi-experimental design with a two-group pretest-posttest approach was used, involving 32 participants selected through total sampling at the Jakarta Hajj Dormitory from October 2023 to May 2024. Participants were divided into two groups: one receiving acupuncture therapy alone, and the other receiving a combination of acupuncture and red ginger steeping. Statistical analysis using the Wilcoxon test yielded a p=0.010, indicating a significant improvement in pain scale and Back Pain Functional Scale (BPFS) scores in both groups after the intervention. The findings suggest that the combination of acupuncture and red ginger steeping is effective in reducing pain and enhancing functional ability in patients with low back pain.